Fast Food Love-themed Ads: Brand Experience in Storytelling - Vergara, Raymond Allan G.; Vergara, Kimberly Christie S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study seeks to understand how the brand experience of Jollibee and McDonald's were co-created through its love-themed ads. Using a case-based approach and a netnographic data collection method, it finds that brand experience may be co-created individually and communally. Brands have many opportunities to engage with and co-create value with their consumers through engaging stories that consumers find relatable.